Liberating co-ops a guide to creating women friendly and gender-responsive co-ops in the Philippines. - Asian Women in Co-operative Development Forum; National Confederation of Co-operatives. (Quezon City Asian Women in Co-operative Development Forum, 1998)
A guiding tool that instructs how to transform gender awareness into action for use by co-ops who wish to address gender inequality in their organization. A companion material "Liberating Co-ops, Stories of Women Friendly and Gender-Responsive Co-operatives in the Philippines" contains stories that show the effects of actions taken from this book.
Jointly published with the National Confederation of Co-operatives with support from Philippines-Canada Human Resource Development (PCHRD) Program.
Keywords: Cooperative societies -- Philippines -- Handbooks, manuals, etc